Rothmund–Thomson Syndrome: novel pathogenic mutations and frequencies of variants in the RECQL4 and USB1 (C16orf57) gene. Issue 3 (24th February 2016) - Suter, Aude‐Annick; Itin, Peter; Heinimann, Karl; Ahmed, Munaza; Ashraf, Tazeen; Fryssira, Helen; Kini, Usha; Lapunzina, Pablo; Miny, Peter; Sommerlund, Mette; Suri, Mohnish; Vaeth, Signe; et al.
Abstract: Background: Poikiloderma is defined as a chronic skin condition presenting with a combination of punctate atrophy, areas of depigmentation, hyperpigmentation and telangiectasia. In a variety of hereditary syndromes such as Rothmund–Thomson syndrome (RTS), Clericuzio‐type poikiloderma with neutropenia (PN) and Dyskeratosis Congenita (DC), poikiloderma occurs as one of the main symptoms. Here, we report on genotype and phenotype data of a cohort of 44 index patients with RTS or related genodermatoses. Methods: DNA samples from 43 patients were screened for variants in the 21 exons of the RECQL4 gene using PCR, SSCP‐PAGE analysis and/or Sanger sequencing. Patients with only one or no detectable mutation in the RECQL4 gene were additionally tested for variants in the 8 exons of the USB1 (C16orf57) gene by Sanger sequencing. The effect of novel variants was evaluated by phylogenic studies, single‐nucleotide polymorphism (SNP) databases and in silico analyses. Results: We identified 23 different RECQL4 mutations including 10 novel and one homozygous novel USB1 (C16orf57) mutation in a patient with PN. Moreover, we describe 31 RECQL4 and 8 USB1 sequence variants, four of them being novel intronic RECQL4 sequence changes that may have some deleterious effects on splicing mechanisms and need further evaluation by transcript analyses. Conclusion: The current study contributes to the improvement of genetic diagnostic strategies and interpretation in RTS and PN that is relevant in order to assess the patients' cancer risk, to avoid continuous and inconclusive clinical evaluations and to clarify the recurrence risk in the families. Additionally, it shows that the phenotype of more than 50% of the patients with suspected Rothmund–Thomson disease may be due to mutations in other genes raising the need for further extended genetic analyses. Abstract : We report on genotype and phenotype data of a cohort of 44 index patients with clinically suspected Rothmund–Thomson syndrome (RTS) or related genodermatoses. We describe 23 different RECQL4 mutations including 10 novel and one homozygous novel USB1 (C16orf57) mutation as well as 31 RECQL4 and 8 USB1 sequence variants. Our study contributes to the improvement of genetic diagnostic strategies and interpretation in RTS and PN that is relevant in order to assess the patients' cancer risk, to avoid continuous and inconclusive clinical evaluations and to clarify the recurrence risk in the families.